2014
DOI: 10.1136/bmjopen-2014-005221
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated significant work limitation in primary care consulters with osteoarthritis: a prospective cohort study

Abstract: ObjectiveTo describe the prevalence of expected work limitations (EWL) prior to future retirement age in osteoarthritis consulters, and the associated health, sociodemographic and workplace factors.DesignPopulation-based prospective cohort study.SettingGeneral practices in Staffordshire, England.Participants297 working adults aged 50–65, who had consulted primary care for osteoarthritis.OutcomeEWL was defined using a single question, “Do you think joint pain will limit your ability to work before you reach 69 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…Individuals were considered to have osteoarthritis if, at that wave or at an earlier wave, they self-reported having been told by a doctor that they have osteoarthritis. (As a gradually progressive chronic condition, osteoarthritis will always remain present following self-reported doctor diagnosis 25 .) Arthritis of an unknown type was assumed to be osteoarthritis as this is the most common form of arthritis 26 .…”
Section: Methodsmentioning
confidence: 99%
“…Individuals were considered to have osteoarthritis if, at that wave or at an earlier wave, they self-reported having been told by a doctor that they have osteoarthritis. (As a gradually progressive chronic condition, osteoarthritis will always remain present following self-reported doctor diagnosis 25 .) Arthritis of an unknown type was assumed to be osteoarthritis as this is the most common form of arthritis 26 .…”
Section: Methodsmentioning
confidence: 99%
“…Osteoarthritis (OA) is the most frequent joint disorder in western societies, and will presumably develop into one of the top-ranking causes of physical functional impairment and disability, including work-related disorders and absenteeism, during the next one or two decades [ 1 – 3 ]. Knee OA is a highly age and sex-associated prevalent and complex disease, with a substantial impact on the quality of life from pain and physical immobility, and consequently a significant limitation in social and working life [ 4 ]. Additionally, the co-morbidity associated with symptomatic knee OA is subject to concern because in a recent study an increased all-cause and disease-specific mortality has been reported in patients with symptomatic and radiographic hip and knee OA [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…61,62 Wilkie and colleagues conducted interviews in 297 English working adults aged 50 to 65, who consulted primary care practitioners due to OA symptoms. 63 The authors concluded that OA was likely to be associated with a 3-fold increased likelihood of not being able to maintain a job. 62,63 A comparison between fiscal analysis and other burden of disease analyses is not straightforward, due to heterogeneity in the former and because they address different economic consequences of OA.…”
Section: Discussionmentioning
confidence: 99%
“…63 The authors concluded that OA was likely to be associated with a 3-fold increased likelihood of not being able to maintain a job. 62,63 A comparison between fiscal analysis and other burden of disease analyses is not straightforward, due to heterogeneity in the former and because they address different economic consequences of OA. A systematic review of burden of disease studies estimated that in European countries the annual direct health-care costs represented close to 20% (€1000/€5100) of total hip and knee OA burden.…”
Section: Discussionmentioning
confidence: 99%